Entre idas e vindas : uma diversidade de sentidos para a escola de EJA - Santos, Juliana Silva dos (2018)
Youth and Adult Education is a topic of debates, controversies, as well as political and social actions addressed to a part of the population that in many cases has already been excluded from regular school. This study aimed to problematize the meanings of diversity for a Youth and Adult Education School in the perspective of young and adult subjects that attend this school. The main objective was to analyze the meanings attributed to Youth and Adult Education schools and the continuity of their studies. Additionally, the present study sought to comprehend the reasons why these individuals return to school in an attempt to give visibility to their concept of time. Furthermore, their perspective regarding their plans and their curriculum conceptions were verified. For data collection, 198 subjects attending 9th, 10th, and 11th grades of Youth and Adult Education at Agrônomo Pedro Pereira State High School in Porto Alegre/RS responded a questionnaire with 56 questions. The program SPSS-18 was used to tabulate data. The participants were 118 women, 79 men, and one non-respondent. The age of 144 subjects ranged from 18 to 29. As some of the reasons to return to school, 87 of the subjects reported graduating faster as the main reason, 38 subjects indicated job-related issues, and 28 subjects pointed to age incompatibility as being an aspect for attending a Youth and Adult Education School. As motivational reasons to keep studying, subjects reported the relationship with their friends and teachers, the desire to obtain more knowledge, and for many, the perspective of a better future linked to studying projects and their relevance. Considering the concept of time for these subjects, many of them revealed that their decision to continue their studies was due to their maturity, which they named moment of inflexion. At this moment, the subjects projected themselves into the future as part of their self-determination. As a result, in order to maintain their studies, other personal projects and some social demands were put aside. Regarding the curriculum conceptions outlined by the respondents, three axes were identified: a curriculum towards work, propaedeutic reasons, and citizenship duties. The subjects demonstrated knowing what they search for and need from school and reported alternative places of education they have attended throughout their life. Along the process of subjectivity of each respondent, there is a plurality of meanings to Youth and Adult Education school. Some of these meanings reinforce the goals of compensation, equalization, and permanent education seen as a public policy towards the Youth and Adult Education model. Other meanings are related to opportunities, not as an effect of a favor that the State should provide for the excluded from school during the proper age, but in a sense of living the right of studying and being part of a scholar community. The metaphor of the Youth and Adult Education model was used as ‘a door to the future’ that defines the sense of Youth and Adult Education as an opportunity to try again, desire a better future, and be the alternative that was left in the moment of inflexion of each of the subjects.